Strength and deformability estimation of centrifuged concrete - Garalevičius, Romualdas; Kliukas, Romualdas; Garalevičius, Adolfas R. (Journal of Civil Engineering and Management, 1996)
Influence of several factors, namely high strength longitudinal reinforcement, transverse (spiral) reinforcement, precompression level and concrete age, on mechanical properties of centrifuged concrete is investigated. It has been established by tests that longitudinal and transverse (spiral) reinforcement make worse compaction, casting and hardening conditions of centrifuged concrete. But the spiral reinforcement reduces transverse deformations of compressed centrifuged members of ring cross-section and hence increases concrete strength. During the experiments for central compression, centrifuged concrete members of a ring cross-section were investigated. The parameters of these members: diameter 260 and 500 mm, height 400 and 800 mm, web thickness 35…80 mm. The specimens were reinforced by longitudinal bars of 10, 12, 14 mm diameter and 4 or 5 mm cross-section spirals. Coefficient of longitudinal reinforcement μ s , varied from 1,5 to 6%, coefficient of transverse reinforcement μ cir —from 0,25 to 1,25%, lead of spirals—from 40 to 100 mm. During testing the ring concrete compressive strength Rb was 30…60 MPa. The results of the above-mentioned experiments are presented in Tables 1, 2 and 3. It is recommended to evaluate the reinforcement influence on mechanical properties of such concrete in members of real constructions by formulas (5) and (6). Relationships of concrete strength, initial modulus of deformation and intensity of precompression (9) and (10) are discussed in this article. The latest test results on relationship between concrete compression, tension strength and concrete age are presented. It is established, that hydration of cement takes quite a long time and compression and tension strength of centrifuged concrete increases. This increase in strength is given in Table 4. The strength of centrifuged concrete of 14, 120, 240 and 360 days was determined by direct compression and tension of concrete rings (Table 4). After 9,600 days (26 years) due to a limited number of specimens (concrete rings) the compressive strength was determined by testing prisms cut from the rings. The tensile strength was determined indirectly—by cutting these prisms, as it is recommended by a standard [11] according to formula (12). The results of these tests are presented in Tables 5 and 6. Theoretical connection between tensile and compressive strength may be described by Ferret formula (13), which we propose to use in a slightly changed form, i. e. as (14). Comparative calculations showed that the centrifuged concrete strength calculated according formula (14) corresponds to the results of direct testing (Table 7). Article in Russian. Оценка прочносто и деформативности центрифугированного бетона Centrifuguotojo betono stiprumo ir deformatyvumo vertinimas Santrauka. Nagrinėjama keleto veiksnių: išilginės stipriosios armatūros, skersinės (spiralinės) armatūros, išankstinio apgniuždymo bei betono amžiaus įtaka centrifuguotojo betono mechaninėms savybėms. Eksperimentais nustatyta, kad išilginė ir skersinė (spiralinė) armatūra blogina centrifuguotojo betono tankinimo ir kietėjimo sąlygas. Tačiau spiralinė armatūra mažina gniuždomų centrifuguotų žiedinio skerspjūvio elementų skersines deformacijas ir taip padidina betono stiprumą. Eksperimentų metu centriniam gniuždymui buvo bandomi centrifuguoti žiedinio skerspjūvio elementai, kurių išorinis diametras lygus 260 ir 500 mm, aukštis 400 arba 800 mm, sienelęs storis 35…80 mm. Bandiniai buvo armuoti išilginiais 10, 12, 14 mm skersmens strypais ir 4 ar 5 mm skersmens spirale. Išilginio armavimo koeficientas μ s keitėsi nuo 1,5 iki 6%, skersinio μ cir —nuo 0,25 iki 1,25%, spirales žingsnis s kito nuo 40 iki 100 mm. Bandant žiedus, jų 14 betono stiprumas gniuždant Rb buvo 30…60 MPa. Minėtų eksperimentų rezultatai pateikti 1, 2 ir 3 lentelėse. Armavimo įtaką tokio betono mechaninėms savybėms realių konstrukcijų elementuose siūloma vertinti (5) ir (6) formulėmis. Straipsnyje aptariamos centrifuguotojo betono stiprio ir pradinio deformacijų modulio priklausomybės (9) ir (10) nuo išankstinio apgniuždymo intensyvumo. Pateikiami naujausi eksperimentiniai duomenys apie betono gniuždomojo ir tempiamojo stiprio priklausomybę nuo jo amžiaus. Nustatyta, kad cementinio akmens hidratacija vyksta pakankamai ilgą. laiką ir centrifuguotojo betono gniuždomasis ir tempiamasis stipris didėja. Šį stiprio prieaugį iliustruoja 4 lentelėje pateikti eksperimentų rezultatai. Centrifuguotojo betono stipris 14, 120, 240 ir 360 parų amžiuje buvo nustatytas tiesiogiai gniuždant ir tempiant žiedus (4 lenteiė). Po 9600 parų (26 metų) dėi riboto bandinių (betonimų žiedų) kiekio gniuždomasis betono stiprumas buvo nustatytas bandant ne ziedus, o iš jų iškirptas prizmes. Tempiamasis stiprumas buvo nustatytas netiesioginiu būdu—kerpant minėtas prizmes, kaip rekomenduoja standartas [11] pagai formulę (12). Šių bandymų rezultatai pateikti 5 ir 6 lentelėse. Teorinis ryšys tarp tempiamojo ir gniuždomojo betono stiprumo gali būti aprašytas Fere (Ferret) formule (13), kurrą centrifuguotojo betono atveju mes siūlome šiek tiek pakoreguotą, t.y. (14). Lyginamieji skaičiavimai parodė, kad pagal (14) formulę nustatytas centrifuguotojo betono skaičiuojamasis stipris atitinka tiesioginių bandymų rezultatus (7 lentelė). First Published Online: 26 Jul 2012